Efeito do Número de Inseminações Artificiais por Ciclo sobre a Fertilidade de Éguas Inseminadas com Sêmen Eqüino Diluído, Resfriado a 20°C e Transportado - Lima, Marcos Chalhoub Coelho; Da Silva Filho, José Monteiro; De Carvalho, Giovanni Ribeiro; Palhares, Maristela Silveira; Valle, Guilherme Ribeiro; Oliveira, Henrique Nunes [UNESP] (My University, 2000)
One hundred and twenty estrus cycles of 105 Mangalarga Marchador breed mares were analyzed to study the effect of number of inseminations per cycle on the fertility of mares inseminated with cooled semen. The mares were randomly allocated in the following group: T1 - one AI/cycle; T2 - two AI/cycle; T3 - tree or more AI/cycle. The cycles were controlled by rectal palpation and teasing. The insemination were made at each 48 hours, from a 30-35 mm follicle diameter until ovulation, with diluted, cooled (20°C) and transported equine semen. The conception rates in the first cycle were, respectively, to T1, T2 and T3, 47.83% (11/23), 70.00% (21/30), and 45.16% (14/31) (P>0,05), and after five cycles were 51.43% (18/35), 48.89% (22/45) and 47.50% (19/40) (P>0,05). The number of AI/cycle had no effect fertility in mares.
Effect of the Number of Insemination per Cycle on Fertility of Inseminated Mares with Diluted Equine Semen, Cooled to 20°C and Transported
Keywords: Equine; Fertility; Number of insemination